Photovoice: A Practical Journey from Theory to Practice - Panlee, Piyarat (Journal of Social Sciences Naresuan University, 2025)
Photovoice is a key visual research method that plays a crucial role in participatory action research (PAR) and community-based research by empowering participants to document their lived experiences and highlight social issues through photography. This approach not only amplifies the voices of marginalized groups but also fosters a sense of ownership in the research process, ultimately driving policy change in a tangible way. This article examinesaddressing ethical considerations and challenges in visual data analysis, which require a systematic approach and collaboration with participants. Additionally, it highlights the future potential of photovoice, particularly in integrating digital technology to expand its applicability across diverse social and cultural contexts. However, implementating photovoice must also account for limitations related to resources, cultural contexts, technological accessibility, and the need for more precise and reliable data analysis frameworks. Therefore, further research on the real-world application of photovoice will help enhance its effectiveness in responding to community needs and reinforce its role as a vital tool for driving sustainable social change.